The ability of Avicennia marina (Api-api putih) to Uptake Heavy Metal of Chromium at Wonorejo Coastal in Surabaya - Herman Pratikno; Harmin Sulistyaning Titah; Handayanu Handayanu; Bintang Respati Dwi Harnani (International Conference on Coastal and Delta Areas, 2017)
The increasing of industries and population growth are the main sources of contamination in the river. Wonorejo river is one of rivers in Surabaya that flow to east coast Surabaya. Concentration of Chromium (Cr) at estuary of Wonorejo River was 0.0325 mg/L and it was 2.7761 mg/L in sediment in 2007. Meanwhile, Cr at east coast of Wonorejo was 0.418 μg/L, it was indicating that upper than standart for biota in sea, 0.005 μg/L (KepMenLH No. 51 tahun 2004). In this research will be measured concentration of Cr from sediment and roots of Avicennia marina at Wonorejo River estuary. And then, it was calculated Bio-consentration Factor (BCF) value of A. marina. Transect method was used to determine the sampling point of mangrove root A. marina and sediment at estuary of Wonorejo River. Mangrove and sediment roots were analyzed using the Atomic Absorption Spectrophotometer (AAS) method, previously samples of roots and sediments were extracted using the wet destruction method. Parameters supporting in this research were measured include temperature using thermometer, salinity using salinometer and pH using pH meter for sediment. Based on the results, the average concentration of Cr in the sediment in transect 1 were 47 mg/kg until to 66.5 mg/kg. The concentration of Cr in roots of A. marina were 28 mg/kg until to 92.25 mg/kg. The BCF value in A. marina were 0.89 to 1.35. Based on the BCF value, it indicated that A. marina was a hyperacumulator species for heavy metals of Cr. Keywords: Avicennia marina, BCF, coast, chromium, root, sediment